Kajian Analisis Wacana: Umat Islam Jangan Terprovokasi - Wendy, Novrizal (Tasamuh: Jurnal Studi Islam, 2020)
This article titled "Muslims are not provoked" shows that Republika journalists interview those who do not support the burning of the Qur'an, they do not interview the pros at all with behavior that is initiated by the wishes of pastor Terrry Jones or even interviewing parties neutral one. Republika reporters wrote the opinions of Hasyim Muzadi and Amidhan at length and wrote the support of several groups without one interviewing parties outside the MUI. Despite the disapproval of the FPI, PGI, or KWI, Republika journalists were not written at all. So that readers do not know the reasons for their rejection. In the analysis of this article, Republika journalists seemed to want to show the influence of Islamic institutions such as the MUI and FPI which were considered to have a great influence in giving strong opinions about the burning of the Qur'an, so their opinions were expected to become a benchmark in taking the attitude and actions of the community in responding to the burning news of Al -Qur'an.